Distribution of E and NS1 proteins of TBE virus in mammalian and tick cells - Senigl, F; Kopecký, J; Grubhoffer, L (Folia microbiologica, 2004)
Four monoclonal antibodies recognizing TBEV proteins were prepared. Three of them (2/H6, 8/A10, 5/F9) specifically recognize the structural E protein and the fourth binds to the nonstructural NS1 protein. These antibodies were used for an immunofluorescence study of TBEV protein distribution in infected mammalian host and tick vector tissue culture cells. Any differences in the distribution of the E and NS1 proteins were revealed. In porcine PS cell line the proteins were localized in the cytoplasm with a distinct increase of the signal in the perinuclear area 16 h post-infection (p.i.). The area gradually expanded and at 24 h p.i. covered the major part of the cytoplasm. The localization of the proteins in tick RA-257 cells revealed a uniform spread of the proteins in whole cytoplasm of the infected cells. The signal was very weak at 16 h p.i. and gradually increased during progressing time p.i., although, the distribution of the proteins did not exhibit any changes. Difference in viral protein distribution in the two cell types points to the possibility that the maturation process of TBEV exhibits different features in mammalian and tick cells.
Keywords: buněčné linie; prasata; Cytoplasm; virové nestrukturální proteiny; Cell Line; proteiny virového obalu; replikace viru; imunohistochemie; Viral Envelope Proteins; fluorescenční mikroskopie; Swine; Viral Nonstructural Proteins; viry klíšťové encefalitidy; Immunohistochemistry; zvířata; Ticks; Microscopy, Fluorescence; Encephalitis Viruses, Tick-Borne; Time Factors; Animals; časové faktory; klíšťata; Virus Replication; cytoplazma